Efeito anti-inflamatório do heparinóide isolado do camarão Litopenaeus vannamei sobre a peritonite aguda - Coelho, Luciana de Figueirêdo (2013)
In recent years the heparin has been the subject of several studies that aim to expand its use as a therapeutic agent, due to its ability to modulate the activity of various proteins that play important roles in the regulation of pathophysiological processes. In several experiments and preclinical trials, heparin has demonstrated an anti-inflammatory role. However, its clinical use is limited, due to its strong anticoagulant activity and hemorrhagic complications. For this reason, considerable efforts have been employed in discovery of heparin analogous (heparinoid) with reduced side effects, that retain the anti-inflammatory properties of heparin. In this context, a heparinoid obtained from the head of Litopenaeus vannamei shrimp, which presents a structural similarity to heparin, showed, in previous studies, anti-inflammatory activity in a model of acute peritonitis with reduced anticoagulant effect in vitro and low hemorrhagic activity. Thus, the present work had as objective to evaluate the effect the heparinoid of the cephalothorax of gray shrimp on the acute inflammatory response in different times (3 or 6 hours after the induction of inflammatory stimulus), using the model of acute peritonitis induced in mice. It was also analyzed the HL effect over the activity of elastase, an enzyme involved in leukocyte recruitment. Furthermore to check if the different doses of heparin and heparinoid change the hemostatic balance in vivo, was assessed the effect of these compounds on the plasma clotting time in animals submitted to inflammation. The results show that in 3 hours, all doses of heparinoid were able to prevent efficiently in the acute inflammatory process without any anticoagulant effects, unlike the extrapolation dose of heparin, which has induced a large hemorrhage due its high anticoagulant activity. However, 6 hours after induction of inflammation, only the dosages of 0.1 and 1.0 μg/Kg of heparin and 1.0 μg/Kg of heparinoid kept anti-migratory effect, without changing of the hemostatic balance. These results indicate that the anti-migratory effect of theses compounds depends on the dosage and time of inflammatory stimulus. The HL and heparin were also able to inhibit the activity of the enzyme elastase. The discovery of this bioactive compound in the cephalothorax of shrimps can arouse great interest in biotechnology, since this compound could be useful as a structural model interesting for the development of new therapeutic agents for peritonitis